Routine clinical measures in a newly commissioned psychiatric intensive care unit (PICU): predictors of favourable outcomes. (1st April 2016) - Carleton, Rebecca; Cordiner, Matthew; Hughes, Patrick; Cochrane, Susan; Shajahan, Polash
Aim: To describe clinical outcomes for patients admitted to a newly opened PICU and to identify and attempt to characterise those patients who did well on specified clinical measures and those who remained unchanged or recorded worsening clinical measures.Method: This was a prospective study from February 2014 to April 2015. For all episodes of patient care, clinical and demographic variables were recorded. Objective assessments of illness severity were measured using the Clinical Global Impression scale (CGI), severity of psychotic symptoms using the Brief Psychiatric Rating Scale (BPRS) and the Zung self-rated depression scale.Results: A total of 69 patients were admitted and discharged during this period. Using the CGI 72% of patients improved, using BPRS 81% improved and using Zung 69% improved. Higher admission CGI, BPRS and Zung Severity scores were associated with improvement according to CGI improvement and BPRS scores. No other variable was associated with improvement.Conclusion: The majority of patients improved, although it is difficult to predict who will do well from demographic or clinical details. It is encouraging that most patients in our survey improved. We plan to use the results to further refine the measuring of clinical effectiveness outcomes of those patients requiring admission to PICU.